Gambaran Tingkat Pengetahuan Ibu Nifas Tentang Perawatan Payudara dan Kelancaran Pengeluaran ASI di Praktik Mandiri Bidan Appi Ammelia - Septi Hanifah; Nendhi Wahyunia Utami (Universitas Harapan Bangsa Purwokerto, 2023)
One of the factors that influence the low level of exclusive breastfeeding is knowledge. Postpartum mothers who have sufficient knowledge and level of understanding of the information received will be quickly captured and understood, including information about breast care during lactation. Knowing the description of the level of knowledge of postpartum mothers about breast care and the smoothness of breastfeeding in the Independent Practice of Midwife Appi Ammelia. This study used a quantitative research design with a cross sectional approach. The population in this study were 26 respondents. Sampling used in this study using total sampling. Collecting data using a questionnaire sheet. Data analysis uses frequency distribution. The results showed that the description of the level of knowledge of postpartum mothers about breast care showed good results (50%) and the smoothness of expressing milk in postpartum mothers showed good results (53.8%). The description of the level of knowledge of postpartum mothers about breast care for postpartum mothers is in the good category and the smoothness of breastfeeding in postpartum mothers is in the smooth category.